An alternative watermarking scheme using sequency ordered hadamard transform (SCHT) - Chong, Nicholas Wei En. (2011)
This report will explore and present the possibility of a new image watermarking scheme using the Real Conjugate Symmetric Sequency-ordered Complex Hadamard Transform (rCS-SCHT). This rCS-SCHT, which has a sequency ordered transform matrix and conjugated symmetric spectrum, has been found to achieve better results in image compression that even surpasses that of the Sequence Ordered Walsh Transform (SOWT) and the Discrete Cosine Transform (DCT) [1].